Thereby hangs a tail [large type] - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery., 2010)
What first seems like a walk in the park to wise and lovable canine narrator Chet and his human companion Bernie<U+2014>to investigate threats made against a pretty, pampered show dog<U+2014>turns into a serious case when Princess and her owner are abducted. To make matters worse, Bernie<U+2019>s on-again, off-again girlfriend, reporter Susie Sanchez, disappears too. When Chet is separated from Bernie, he<U+2019>s on his own to put the pieces together, find his way home, and save the day.